Damage assessment of channel section columns subjected to uniform compression. (15th October 2018) - Gliszczynski, A.; Jakubczak, P.; Kubiak, T.; Bienias, J.
Abstract: The paper presents the failure analysis of compressed channel section profile made of GFRP material. Three symmetrical arrangements of layers were considered: [90/0/90/0]s, [90/-45/45/0]s, [45/-45/90/0]s. In order to characterize the failure process, visual inspection, ultrasonic phased array, non-destructive testing and computer microtomography were used. Damage analysis based on studies of external and internal damage of investigated structure allowed for identification of characteristic failure modes and mechanisms. It was shown that the dominant form of destruction in the quasi-orthotropic system are matrix cracks coupled with the presence of extensive delamination while in quasi-isotropic systems more concentrated damage was noticed, in which the cracking/rapture of fibers localized in the column's corners determined the initiation of the failure mechanism and the carrying capacity loss. In addition, it was noted that the fiber directions of the outer layers determined the directions of matrix cracks and delamination propagation.